An Evaluation and Critique of Encyclopedia of New Religious Movements - Hadi Vakili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Encyclopedia of new religious movements edited by Peter B. Clarke provides a truly engaging and authentic view of the emerging religious movements on a background of the universe. This encyclopedia, containing 428 articles from leading academics, studies the remarkable examples of religious movements emerging in each continent. Clarke as an editor has written a higher income as "New Religions as a global phenomenon", a "Resource guide of NRM" and a useful article entitled "Typology of new religions" in this encyclopedia. This encyclopedia is a leading, research, updating, important, and valuable reference for academic libraries. However, the encyclopedia suffers from some disadvantages, among which we can refer to apparent contradictions in Index, the incidence of historical errors, print, etc., in its context and putting NRM identified with the Cults, sects, and counter-culture groups